2013
DOI: 10.1371/journal.pone.0056398
|View full text |Cite
|
Sign up to set email alerts
|

Permissive Summer Temperatures of the 2010 European West Nile Fever Upsurge

Abstract: BackgroundIn the summer of 2010, Europe experienced outbreaks of West Nile Fever (WNF) in humans, which was preceded by hot spells. The objective of this study was to identify potential drivers of these outbreaks, such as spring and summer temperatures, relative humidity (RH), and precipitation.MethodsPearson and lag correlations, binary and multinomial logistic regressions were used to assess the relationship between the climatic parameters and these outbreaks.ResultsFor human morbidity, significant (<0.05) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(151 citation statements)
references
References 39 publications
4
142
0
5
Order By: Relevance
“…Among other variables, the average maximum relative humidity was associated with vector population dynamics [60]. A recent analysis detected correlations between morbidity in humans and weekly relative humidity in Europe and western Asia [22]. All these studies found that air temperature is a better predictor for increasing disease cases than air humidity.…”
Section: (C) Relative Humiditymentioning
confidence: 99%
See 4 more Smart Citations
“…Among other variables, the average maximum relative humidity was associated with vector population dynamics [60]. A recent analysis detected correlations between morbidity in humans and weekly relative humidity in Europe and western Asia [22]. All these studies found that air temperature is a better predictor for increasing disease cases than air humidity.…”
Section: (C) Relative Humiditymentioning
confidence: 99%
“…However, it was shown that the replication cycle is completed more quickly in mosquitoes at higher temperatures [38,39], while a clear association was found between extreme heat and outbreak intensity in humans [4,18,22,35,[40][41][42][43]. At the same time, it is important to note that, in some cases, extremely high temperatures begin to slow down mosquito activity.…”
Section: (A) Temperaturementioning
confidence: 99%
See 3 more Smart Citations